Pathological and biochemical studies on experimental poisoning of sheep by cocklebur (xanthium strumarium L.subsp. cavanillesii) - Karadaş, Erkan; Yaman, Ihsan; Özdemir, Necmi (Scientific and Technical Research Council of Turkey, 1997)
Cocklebur toxicosis was induced experimentally in Akkaraman lamsb. 14, 15-months-old 16 lambs were divided into 4 groups each consisting of 4 lambs. 1-3 leaves of Xanthium strumarium L.subsp. cavanillesii shoots were cut into pieces in the size of a straw and mixed with straw containing 300 g/kg crushed barley as follow; 0 % (group I-control group), 40 % (group II). 60 % (group III) and 80 % (group IV). The fresh and daily prepared ration (2200 g/day) was given to each animal for a period of 10 weeks. Total death rate for all trial groups was recorded as 25 %. Although neither considerable clinical nor morphological and biochemical findings were detected in animals in group II. these findings in question were striking in animals in group III and group IV. The most important clinicial findings were reduction in weight gain and the dark-yellowish brown appearence of wool together with excessive perspiration. In addition, steadily gnashing teeth were also noticed Typical gross lesions were ascites. fullness of gallbladder and urinary bladder and edema of their walls. Widespread fibrin masses were on the surface pancreas, spleen and liver, resulting in adhesion in lobes. Furthermore, intense edema in the ligamentum hepatogastricum and centrilobular accentuation which was most apparent on cut surfaces of the liver were also observed. Enlargement of testicles, bilateral edematous appearence, loose consistency and soft structure were common macroscopic manifestations of testicular degeneration. Microscopic findings were in aggrement with macroscopic lesions. Results of biochemical tests showed a pronounced rise in serum glutamic oxalacetic transaminase, serum glutamic pyruvic transaminase. alkaline phosphatase. isositric dehydrogenase and gamma glutamyl transpeptitase levels (P<0.001) along with hypoglycemia (P<0.001). There was a prominent drop in total protein and albumin levels (P<0.001). The presence of effective toxic substance carboxyatractyloside in plant shoots, tissue and urine samples of experimental animals was demonstrated qualitatively (Rf = 0.6) by toxicologie studies.
Koyunlarda Deneysel Pitrak Otu (Xanthium strumarium L. subsp. cavanillesii-Cocklebur) Toksikasyonu Üzerine Patolojik ve Biyokimyasal Araştirmalar
Keywords: Akkaraman lambs; Cocklebur; Morphology